2004
DOI: 10.1111/j.0022-202x.2004.22701.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of GVHD-Like Skin Disease by Passively Transferred CD8+ T-Cell Receptor Transgenic T Cells into Keratin 14-Ovalbumin Transgenic Mice

Abstract: To understand the mechanisms involved in immunological tolerance to skin-associated antigens, we have developed transgenic (Tg) mice that express a model self-antigen, membrane-bound chicken ovalbumin (OVA), under the control of a keratin 14 (K14) promoter. K14-mOVA Tg mice express OVA mRNA in the epidermis, and appear normal. K14-mOVA Tg mice failed to mount T cell and delayed type hypersensitivity reactions to OVA, suggesting that the Tg mice were tolerant to OVA. Skin dendritic cells, including Langerhans c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 32 publications
3
106
1
1
Order By: Relevance
“…Our results are supported by two recent reports. Shibaki et al (29) used mice expressing the whole OVA protein under the K14 promoter and showed that DCs emigrating from skin explants cross-presented OVA peptides. DCs emigrating from whole skin explants are a mixture of dermal DCs and LCs (30), and therefore, the relative contribution of LCs could not be determined in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are supported by two recent reports. Shibaki et al (29) used mice expressing the whole OVA protein under the K14 promoter and showed that DCs emigrating from skin explants cross-presented OVA peptides. DCs emigrating from whole skin explants are a mixture of dermal DCs and LCs (30), and therefore, the relative contribution of LCs could not be determined in this report.…”
Section: Discussionmentioning
confidence: 99%
“…The LC paradigm has been expanded to include LC that migrate to skin-draining LN in the steady state in the absence of activating stimuli where they present self-peptides to T cells [10][11][12][13][14]. This steady-state presentation of self-antigens has been proposed to eliminate self-reactive T cells and provide a mechanism of peripheral tolerance [15,16].…”
Section: Mini-reviewmentioning
confidence: 99%
“…In addition, they dramatically upregulate their surface expression of co-stimulatory molecules and start to produce cytokines required for proper Th1 or Th2 instruction. Thus, by the time LC arrive in the LN, they have acquired the surface phenotype of a 'functionally' mature DC capable of activating naive T cells and thereby initiating an adaptive immune response specifically tailored to fight off the invading cutaneous pathogen [5].The LC paradigm has been expanded to include LC that migrate to skin-draining LN in the steady state in the absence of activating stimuli where they present self-peptides to T cells [10][11][12][13][14]. This steady-state presentation of self-antigens has been proposed to eliminate self-reactive T cells and provide a mechanism of peripheral tolerance [15,16].…”
mentioning
confidence: 99%
“…We used a pCMV␤ expression vector (Invitrogen, Carlsbad, CA) that contained the cytomegalovirus (CMV) promoter, the simian virus 40 (SV40) splice donor/splice acceptor site, the lacZ gene, and the SV40 polyadenylation signal. We selected human keratin 14 (K14), 10 the mouse pro-␣ 2 chain of type I collagen (col1a2), 11 or the CMV promoter for epidermis-specific, dermis-specific, or ubiquitous expression of the transgene, respectively. We first modified pCMV␤ by replacing LacZ with human fulllength COL7A1 cDNA, and the CMV promoter with the human K14 or the mouse col1a2 gene.…”
Section: Generation Of Transgenic Micementioning
confidence: 99%
“…10,11 The mice with K14 or col1a2 promoters were designated as K14Tg mice (COL7 K14-hϩ ) and col1a2Tg mice (COL7 col1-hϩ ), respectively ( Figure 1A). In addition, the ubiquitous CMV promoter was used to generate transgenic mice with both epidermal and dermal expression (CMVTg mice: COL7 CMV-hϩ ) ( Figure 1A).…”
Section: Generation Of Transgenic Mice Showing Keratinocyte-or Fibrobmentioning
confidence: 99%